The problems of assessing the value of mergers and acquisitions - Borovikov A. D. (Interactive science, 2017)
the article discusses some questions concerning mergers and acquisitions of companies. The essential foundation of any mergers and acquisitions is always the competitive environment, more precisely, its constant changes.
Keywords: Компания; мотивы; конкуренция; competition; Company; слияние; motives; поглощение; merger; acquisition